Characteristically Near Stable Vector Fields in the Polar Complex Plane - Enze Cui; James F. Peters (Communications in Advanced Mathematical Sciences)
This paper introduces results for characteristically proximal vector fields that are stable or non-stable in the polar complex plane $\mathbb{C}$. All characteristic vectors (aka eigenvectors) emanate from the same fixed point in $\mathbb{C}$, namely, 0. Stable characteristic vector fields satisfy an extension of the Krantz stability condition, namely, the maximal eigenvalue of a stable system lies within or on the boundary of the unit circle in $\mathbb{C}$. An application is given for stable vector fields detected in motion waveforms in infrared video frames. AI is used to separate the changing from the unchanging parts of each video frame.